Compensatory Mechanisms Modulate the Neuronal Excitability in a Kainic Acid-Induced Epilepsy Mouse Model - Pan, Gaojie; Chen, Zhicai; Zheng, Honghua; Zhang, Yunwu; Xu, Huaxi; Bu, Guojun; Zheng, Hui; Li, Yanfang (Frontiers in Neural Circuits, 2018)
Epilepsy is one of the most common neurological disorders affecting millions of people. Due to the complicated and unclear mechanisms of epilepsy, still a significant proportion of epilepsy patients remain poorly controlled. Epilepsy is characterized by convulsive seizures that caused by increased excitability. In this study, by using KA-induced epilepsy mice, we investigated the neuronal activities and revealed the neuronal compensatory mechanisms after KA-induced toxic hyperexcitability. The results indicate that both phasic inhibition induced by enhanced inhibitory synaptic activity and tonic inhibition mediated by activated astrocytes participate in the compensatory mechanisms. Compensatory mechanisms were already found in various neuronal disorders and were considered important in protecting nervous system from toxic hyperexcitability. This study hopefully will provide valuable clues in understanding the complex neuronal mechanisms of epilepsy, and exploring potential clinical treatment of the disease.